135k views
0 votes
The present age of Sahil’s mother is three times the present age of Sahil.

After 5 years their ages will add to 66 years. Find their present ages.

User Xoux
by
4.7k points

2 Answers

6 votes

Explaination :

So here this question is of concept linear equations. As in linear equations we assumes the unknown number as an variable. Here also we would be doing same.!!

So let us assume the present age of Sahil as n and present age of his mother as m.

Now, in the question it is given that present age of Sahil’s mother is three times the present age of Sahil. So we would keep age of Sahil's mother equal to the three times of Sahil's age.

Present age of Sahil's mother = 3 (Sahil age)

Putting the values,

m = 3(n)

m = 3 × n

m = 3n

After 5 years,

After 5 years age of Sahil and his mother would be :

  • Age of Sahil = n + 5
  • Age of Sahil's mother = m + 5

Age of Sahil + Age of his mother = 66

(n + 5) + (m + 5) = 66

n + 5 + m + 5 = 66

n + m + 10 = 66

n + m = 66 - 10

n + m = 56

m = 56 - n

Putting the value of m here.,

3n = 56 - n

3n + n = 56

4n = 56

n = 56 / 4

n = 28 / 2

n = 14

Therefore,

  • Value of n is 14.

And,

  • m = 56 - n
  • m = 56 - 14
  • m = 42

Henceforth,

  • Present age of Sahil is 14 years
  • Present age of Sahil's mother is 42 years.

User Oscar Urueta
by
4.8k points
3 votes

Answer:

  • Sahil's mother = 42 years
  • Sahil = 14 years
    .

Step-by-step Explanation:

Let the age of Sahil's mother be x and the age of Sahil be y. Then according to question.

• Sahil's mother age = 3(Sahil's age)

➛ x = 3y -----------(1)

And according to second condition,

• Sahil's mother age + 5 + Sahil's age + 5 = 66

➛ x + 5 + y + 5 = 66

➛ x + y + 10 = 66

➛ x + y = 56 ----------(2)

Now substituting x = 3y in equation (2)

➛ 3y + y = 56

➛ 4y = 56

➛ y = 14

Then,

➛ x = 3(14) = 42

Hence:-

  • Present age of Sahil's mother is 42 years and Present age of Sahil is 14 years.
User Ville
by
5.2k points